2015
DOI: 10.1159/000442504
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cytogenetics in Digenean Parasites: Linked and Unlinked Major and 5S rDNAs, B Chromosomes and Karyotype Diversification

Abstract: Digenetic trematodes are the largest group of internal metazoan parasites, but their chromosomes are poorly studied. Although chromosome numbers and/or karyotypes are known for about 300 of the 18,000 described species, molecular cytogenetic knowledge is mostly limited to the mapping of telomeric sequences and/or of major rDNA clusters in 9 species. In this work we mapped major and 5S rDNA clusters and telomeric sequences in chromosomes of Bucephalus minimus, B. australis, Prosorhynchoides carvajali (Bucephalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
2
1
Order By: Relevance
“…H. elongata karyotype consists of two pairs of large chromosomes and 10 pairs of smaller-sized chromosomes. In contrast with a previous reports collected and analysed by Garcia-Souto and J. Pasantes [ 41 ] where single loci of major rDNA clusters are described in several digeneans, we revealed multiple signals of rDNA at 3 chromosome pairs in H. elongata karyotype. The lack of karyological data on the other Himasthla species doesn’t allow any speculation about chromosome number characteristic for this genus.…”
Section: Discussioncontrasting
confidence: 99%
“…H. elongata karyotype consists of two pairs of large chromosomes and 10 pairs of smaller-sized chromosomes. In contrast with a previous reports collected and analysed by Garcia-Souto and J. Pasantes [ 41 ] where single loci of major rDNA clusters are described in several digeneans, we revealed multiple signals of rDNA at 3 chromosome pairs in H. elongata karyotype. The lack of karyological data on the other Himasthla species doesn’t allow any speculation about chromosome number characteristic for this genus.…”
Section: Discussioncontrasting
confidence: 99%
“…The B chromosomes are known to be non-essential supernumerary elements present in thousands of plant, animal, and fungal species [ 32 ] and have also been described in some digenean parasites [ 21 , 69 ]. Comparison of their molecular composition has shown that most DNA sequences found on B chromosomes are also present on A chromosomes [ 12 ], and although mainly repetitive DNA is found on them [ 8 ], protein-coding genes have also been discovered [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although those differences could indicate variations in chromosome numbers among different genera in the family, as the divergent diploid numbers (30 and 36) for three of these species were determined from paraffinned material in a study performed in the early 1960s [ 5 ], it would be necessary to confirm them using modern techniques of chromosome preparation. In regard to the highly divergent diploid chromosome number of 2n = 16 proposed for E. subnodosa [ 13 ], it is important to take into account that gastropod mollusks are usually intermediary hosts for digenean parasites, many of which present chromosome numbers and karyotypes [ 30 ] similar to the one reported for E. subnodosa [ 13 ]. Thus, future studies are needed to confirm the chromosome number in this species.…”
Section: Discussionmentioning
confidence: 99%